A complete set of NMR chemical shifts and spin-spin coupling constants for L-Alanyl-L-alanine zwitterion and analysis of its conformational behavior - Bour, Petr; Budesínský, Milos; Spirko, Vladimír; Kapitán, Josef; Sebestík, Jaroslav; Sychrovský, Vladimír (Journal of the American Chemical Society, 2005)
With the aid of labeling with stable isotopes ((15)N and (13)C) a complete set of chemical shifts and indirect spin-spin coupling constants was obtained for the zwitterionic form of L-alanyl-L-alanine in aqueous solution. Different sensitivities of the NMR parameters to the molecular geometry were discussed on the basis of comparison with ab initio (DFT) calculated values. An adiabatic two-dimensional vibrational wave function was constructed and used for determination of the main chain torsion angle dispersions and conformational averaging of the NMR shifts and coupling constants. The quantum description of the conformational dynamics based on the density functional theory and a polarizable continuum solvent model agrees reasonably with classical molecular dynamics simulations using explicit solvent. The results consistently evidence the presence of a single form in the aqueous solution with equilibrium main chain torsion angle values (psi = 147 degrees, varphi = -153 degrees), close to that one found previously in an X-ray study. Under normal temperature the torsion angles can vary by about 10 degrees around their equilibrium values, which leads, however, to minor corrections of the NMR parameters only. The main chain heavy atom chemical shifts and spin-spin coupling constants involving the alpha-carbon and hydrogen atoms appear to be most useful for the peptide structural predictions.
Keywords: Thermodynamics; konformace proteinů; povrchové vlastnosti; Solutions; roztoky; voda; dipeptidy; Models, Molecular; Water; Nuclear Magnetic Resonance, Biomolecular; Protein Conformation; Dipeptides; molekulární modely; termodynamika; nukleární magnetická rezonance biomolekulární; Surface Properties